Creative capacity for sustainable development: A comparative analysis of European and Turkish rural regions - Aliye Ahu Gulumser; Tuzin Baycan-Levent; Peter Nijkamp (European Regional Science Association (ERSA), 2010)
Creative capacity in the field of regional sciences means the capability of any region to generate knowledge and thus to achieve innovation and the diffusion of the output of the innovative activity while obtaining the viability and sustainability of this process. Although creative capacity studies mainly focus on urban regions, the late rural studies and empirical evidences showed that rural region has a great potential capacity in terms of its five components viz. knowledge; innovation; entrepreneurship; creativity; and networks. But, these opportunities have shown by a rural specific approach rather than an urban approach. On this basis, by taking into consideration these discussions in the literature, we assume that the rural creative capacity can be evaluated by the recent changes in rural regions that show the capability of rural regions to exploit its knowledge as an output. On this purpose, in this study, we aim to evaluate which component is relatively important to identify the level of rural creative capacity. Therefore, the study focuses on 60 villages from Europe and 17 villages from Turkey by deploying the data obtained from the in-depth questionnaires. This study is a first attempt at settlement level with an optimistic approach to measure the opportunities lying at the heart of rural regions. The results of the study showed that creativity in terms of traditions is the most important component in both cases while European villages have more opportunities and do not have the latent rural problems while Turkish villages are still suffering from the well-known rural problems that their capacity exists but it is very limited.
Keywords: 330